A semi-selective medium to isolate and identify bacteria of the genus Pantoea - Kini, K.; Dossa, R.; Dossou, B.; Mariko, M.; Koebnik, R.; Silué, D. (Springer, 2019)
The isolation, purification and accurate diagnosis of Pantoea and many other bacterial species that infect rice are essential for upstream studies. However, some isolates of Pantoea and other bacteria such as Sphingomonas have similar biochemical and morphological features on common culture media and are thus difficult to isolate selectively and accurately diagnose. We thus developed a semi-selective medium containing 65 g/l (65%) NaCl that allows growth of all Pantoea strains, but inhibits other microorganisms. It can be used to isolate and purify Pantoea spp. for preliminary diagnosis.